Can creatine supplementation interfere with muscle strength and fatigue in brazilian national level paralympic powerlifting? - Sampaio, C. R. S. F.; Aidar, F. J.; Ferreira, A. R. P.; dos Santos, J. L.; Marçal, A. C.; de Matos, D. G.; de Souza, R. F.; Moreira, O. C.; Guerra, I.; Filho, J. F.; Marcucci-Barbosa, L. S.; Nunes-Silva, A.; et al. (Nutrients, 2020)
The aim of the present study was to analyze the effect of creatine (Cr) supplementation on peak torque (PT) and fatigue rate in Paralympic weightlifting athletes. Eight Paralympic powerlifting athletes participated in the study, with 25.40 ± 3.30 years and 70.30 ± 12.15 kg. The measurements of muscle strength, fatigue index (FI), peak torque (PT), force (kgf), force (N), rate of force development (RFD), and time to maximum isometric force (time) were determined by a Musclelab load cell. The study was performed in a single-blind manner, with subjects conducting the experiments first with placebo supplementation and then, following a 7-day washout period, beginning the same protocol with creatine supplementation for 7 days. This sequence was chosen because of the lengthy washout of creatine. Regarding the comparison between conditions, Cr supplementation did not show effects on the variables of muscle force, peak torque, RFD, and time to maximum isometric force (p > 0.05). However, when comparing the results of the moments with the use of Cr and placebo, a difference was observed for the FI after seven days (U3: 1.12; 95% CI: (0.03, 2.27); p = 0.02); therefore, the FI was higher for placebo. Creatine supplementation has a positive effect on the performance of Paralympic powerlifting athletes, reducing fatigue index, and keeping the force levels as well as PT.